Bidirectional Longitudinal Relations Between Parent–Grandparent Co-parenting Relationships and Chinese Children’s Effortful Control During Early Childhood - Li, Xiaowei; Zhou, Siyu; Guo, Yuanfang (Frontiers in Psychology, 2020)
Parent-grandparent co-parenting has become a common mode in Chinese families; however, its correlation with children’s development from a long run remains unclear. Herein, a 10-month follow-up survey was conducted among 253 preschool children and their parents from Chinese parent-grandparent co-parenting families. It aimed to examine the bidirectional longitudinal correlation of children’s effortful control with mother-grandparent and father-grandparent co-parenting relationships, as well as the dissimilarity of the two co-parenting relationships. In addition, the moderating role of maternal parenting self-efficacy in these relations was also investigated. Cross-lagged model showed that: (1) mother-grandparent co-parenting relationship (T1) positively predicted father-grandparent co-parenting relationship (T2). (2) dissimilarity of mother-grandparent and father-grandparent co-parenting relationships (T1) negatively predicted children's effortful control (T2). (3) maternal parenting self-efficacy significantly moderated the predictive effect of children's effortful control on father-grandparent co-parenting relationship. However, further simple slope analysis showed that after controlling father-grandparent co-parenting relationship (T1), children's effortful control (T1) didn’t significantly predict father-grandparent co-parenting relationship (T2) either in high or low maternal parenting self-efficacy group. These results indicated that, in Chinese parent-grandparent co-parenting families, father-grandparent co-parenting relationship was influenced by mother-grandparent co-parenting relationship; and similar mother-grandparent and father-grandparent co-parenting relationships were conducive to the development of children's effortful control.